PCR and DGGE Detection Limits for Wine Spoilage Microbes - Bester, L.; Cameron, M.; du Toit, M.; Witthuhn, R.C. (South African Journal of Enology and Viticulture, 2016)
In this study the culture-independent technique, polymerase chain reaction (PCR)-denaturing gradient gel electrophoresis (DGGE), was investigated for the early detection and identification of possible spoilage microbes in wine. PCR and DGGE conditions were successfully optimised with the universal primers HDA1GC and HDA2, the bacteria-specific primers WBAC1GC-WBAC2, and the yeast-specific primers NL1GC and LS2. PCR and DGGE detection limits were determined for Lactobacillus plantarum, Pediococcus pentosaceus, Acetobacter pasteurianus and Brettanomyces bruxellensis when inoculated into sterile saline solution (SSS) and white wine at 106 cfu/mL respectively. PCR detection limits were more sensitive (101 to 102 cfu/mL) than DGGE detection limits (101 to 104 cfu/ mL), with the exception of B. bruxellensis, which had higher PCR and DGGE detection limits than the other reference microbes. PCR-DGGE analysis was also used successfully to detect and identify Lb. plantarum, A. pasteurianus and B. bruxellensis at a concentration of 108 cfu/mL as part of mixed populations in SSS and white wine. PCR detection limits of 101 cfu/mL were determined for all three reference microbes in mixed populations. The DGGE detection limits were higher for mixed populations when compared to single strains.